The TRIAD Assisting, Advising, and Assessment Model: One Institution's Attempt to Support the Student-Athlete - Stier, Jr., William F. (My University, 1992)
The Triad Assisting, Advising, and Assessment Model is a multifaceted approach to meeting the needs of young men and women who are placed in the dual roles of college student and athlete. Student-athletes face numerous pressures, on and off campus, both real and perceived. To enable student-athletes to successfully meet these pressures and challenges, the State University of New York, Brockport, has instituted the Triad Model. The model, depicting a methodology of academic, personal, and athletic advising, utilizes an approach which has both traditional and innovative components.
Keywords: models; Division III